Biomarkers In Orthodontic Tooth Movement - Manmohan, Sagarika; N K, Lokesh; S, Vaishnavi; L Bharadwaj, Keerthana; Patil, Nag Nachiket (Journal of Neonatal Surgery, 2025)
Orthodontic tooth movement is a complex process of various mechanisms bringing about remodeling changes in periodontium, alveolar bone and gingiva. This process occurs as a response to the mechanical forces applied onto the teeth by orthodontic appliances which gets transmitted to the alveolar bone, periodontal ligament and gingival tissue. These tissues undergo adaptive changes and result in movement of the teeth to their desired positions. The exact mechanisms of the changes occurring at cellular level is of great interest and importance in modern orthodontic practice. The orthodontists can better understand the mechanisms of action and the significance of various biomarkers to have clear insight into the phases of tooth movement, site and nature of force applied and its impact on the alveolar tissues, the response of the tissues to forces applied on the teeth and the continuous process of bone remodeling even after cessation of active orthodontic tooth movement. the gingival crevicular fluid (GCF) is a medium of study of these processes as it contains concentrations of biomarkers that reflect the underlying process of tissue adaptation. GCF can be collected from patients using filter paper strips, gingival washings, platinum loops and micropipettes. Analyzing the GCF can reveal its composition and the various biomarkers present in it. The orthodontist can use this to understand the intricate details of bone remodeling and make proper choice of mechanical force application to shorten orthodontic treatment time and avoid adverse effects of improper force application